2023
DOI: 10.1002/gps.6033
|View full text |Cite
|
Sign up to set email alerts
|

Does eating with others promote happiness among older adults living alone? A 3‐year longitudinal study of the Japan gerontological evaluation study

Hequn Wang,
Taishi Tsuji,
Kazushige Ide
et al.

Abstract: ObjectiveLiving a happy life is an essential issue for old adults. However, how eating with others contributes to happiness and whether this association is different by living arrangements or not is unknown. The current study examined the relationship between the frequency of eating with others and happiness among older adults according to their living arrangements using 3‐year longitudinal data.MethodsThe analyzed sample comprised 18,727 people (10,920 males and 7807 females) with low happiness (0–7 points on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The previous studies have reported that eating alone is associated with adverse health outcomes in older adults. Eating alone increases the risk of depressive symptoms [ 43 , 44 ], and the Japan Gerontological Evaluation Study reported that a higher frequency of eating with others resulted in happiness in older adults [ 45 ]. In older women, eating alone has been associated with angina [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have reported that eating alone is associated with adverse health outcomes in older adults. Eating alone increases the risk of depressive symptoms [ 43 , 44 ], and the Japan Gerontological Evaluation Study reported that a higher frequency of eating with others resulted in happiness in older adults [ 45 ]. In older women, eating alone has been associated with angina [ 15 ].…”
Section: Discussionmentioning
confidence: 99%